Technological progress, non-price factors competitiveness, and changes in trade income elasticities: empirical evidence from South Korea and Hong Kong. Issue 1 (April 2021) - Resende, Marco Flávio Cunha; Leone, Vitor; Torres, Daniela Almeida Raposo; Coleman, Simeon
Abstract : In the balance-of-payments-constrained growth model literature, income elasticities (IEs) are considered as the crucial element determining a country's long-run growth rate. Although the extant literature accepts that technology matters for IEs magnitude, explanations linking technology and IEs magnitude are limited. In this paper, we make use of the National Innovation System (NIS) concept from the Evolutionary School to explain the channels through which the size of a country's IEs is influenced by the level of development of its NIS, which in turn is a channel through which the non-price competitiveness factors work. Additionally, we empirically test the hypothesis that the catch-up allowed by NIS developments achieved in South Korea and Hong Kong improved their IEs over the 1980–1995 period. Our empirical results suggest a link between the level of NIS development and the size of the IEs.